FerrLegal Transendence Theory: Traces and Efforts to Build Transendent Legal Paradigm - Achmad Dzaki Prasetyo; Dwi Agustina Maharani; Ertina Dewi Setyaningrum; Strong Ari Febrianto; Nadzirah Nurul Hanan (Proceeding International Conference Restructuring and Transforming Law, 2022)
Extradition between Indonesia and Singapore began to be signed on January 25, 2022 in Bintan, Riau Islands. In this extradition agreement, the implementation that has been carried out by the two countries in the arrest of perpetrators of criminal acts allows prisoners who have fled to Singapore or Indonesia to be returned to their respective countries and can be tried in the country where they committed the crime. In this study, the author uses a normative juridical method and through a literature study, the researcher collects literature studies originating from national and international writings, journals or articles that have relevance and are in accordance with what is needed to support research.